2018
DOI: 10.1111/bpa.12655
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease and type 2 diabetes mellitus are distinct diseases with potential overlapping metabolic dysfunction upstream of observed cognitive decline

Abstract: Alzheimer's disease (AD) and type-2 diabetes mellitus (T2DM) are highly prevalent aging-related diseases associated with significant morbidity and mortality. Some findings in human and animal models have linked T2DM to AD-type dementia. Despite epidemiological associations between the T2DM and cognitive impairment, the interrelational mechanisms are unclear. The preponderance of evidence in longitudinal studies with autopsy confirmation have indicated that vascular mechanisms, rather than classic AD-type patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 205 publications
0
75
1
2
Order By: Relevance
“…Nearly one‐half of postmenopausal women develop osteoporosis, but menopause also increases incidence of other comorbidities including coronary artery disease, certain cancers, chronic obstructive pulmonary disease, stroke, and dementia . It is tempting to speculate that the proinflammatory T cells produced by E 2 loss also contribute to the pathogenesis of these conditions because all these conditions are known to be caused by both chronic inflammation and metabolic syndrome . In conclusion, our studies establish a new regulatory circuit between E 2 , the immune system, and the skeletal system.…”
Section: Discussionmentioning
confidence: 69%
“…Nearly one‐half of postmenopausal women develop osteoporosis, but menopause also increases incidence of other comorbidities including coronary artery disease, certain cancers, chronic obstructive pulmonary disease, stroke, and dementia . It is tempting to speculate that the proinflammatory T cells produced by E 2 loss also contribute to the pathogenesis of these conditions because all these conditions are known to be caused by both chronic inflammation and metabolic syndrome . In conclusion, our studies establish a new regulatory circuit between E 2 , the immune system, and the skeletal system.…”
Section: Discussionmentioning
confidence: 69%
“…Next, we investigated other causative factor such as inflammatory process, mitochondrial dysfunction, or oxidative stress that may have a more critical role in the synaptic and cognitive deficits in T2DM (Carvalho et al, ; Chornenkyy, Wang, Wei, & Nelson, ; Ling et al, ; Pintana et al, ; Tumminia, Vinciguerra, Parisi, & Frittitta, ; Verdile et al, ). In addition, others authors have shown that db/db mice have reductions in brain weight and spine density, which were worsened in APP/PS1xdb/db mice, indicating a role for Aβ in these deficits (Infante‐Garcia, Ramos‐Rodriguez, Galindo‐Gonzalez, & Garcia‐Alloza, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of these links may lie in the fact that T2DM usually leads to atherosclerosis, which mediates cognitive decline. Another may lie in the alterations to cerebral glucose metabolism, as suggested by Chornenkyy et al [38]. Evidence from studies such as the Baltimore Longitudinal Study of Aging have shown, through autopsy, that glucose metabolism is altered in the orbital and prefrontal cortex, temporal cortex (middle gyrus, parahippocampal gyrus, and uncus), and cerebellar regions in cases of Alzheimer's disease [39,40].…”
Section: Diabetes and Dementiamentioning
confidence: 97%